2019
DOI: 10.1002/ett.3787
|View full text |Cite
|
Sign up to set email alerts
|

An effective handover management based on SINR and software‐defined network over urban vehicular ad hoc networks

Abstract: Urban vehicular ad hoc network (UVANET) is a modality of high-topology variation MANET where vehicles travel across constrained layout of the roads and tall buildings, which eventually results in shadowing effects. One of the critical challenges in UVANET is the handover process that happens when a vehicle changes its association with the roadside unit. Urban area suffers from high vehicular density at traffic signals, and vehicle slowdowns caused by speed limits, frequent link disconnection caused by signal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…However, with existing networks, these connections will be prone to frequent disruptions arising from insufficient support for high mobility broadband services. Improved mobility management (Imran et al, 2019a;Ozturk et al, 2019;Tabassum et al, 2019) and proactive handover (HO) optimization techniques (Ahmed and Alzahrani, 2019;Mollel et al, 2019;Mollel et al, 2020) are required for consistent quality of service along highways or speed train routes.…”
Section: Service Disruptionsmentioning
confidence: 99%
“…However, with existing networks, these connections will be prone to frequent disruptions arising from insufficient support for high mobility broadband services. Improved mobility management (Imran et al, 2019a;Ozturk et al, 2019;Tabassum et al, 2019) and proactive handover (HO) optimization techniques (Ahmed and Alzahrani, 2019;Mollel et al, 2019;Mollel et al, 2020) are required for consistent quality of service along highways or speed train routes.…”
Section: Service Disruptionsmentioning
confidence: 99%
“…Omheni et al 47 suggested a vertical MIH / PMIPv6‐based handover protocol for optimization, introducing an early resource management, authentication, resource reservation, and IP allocation method. They identified two thresholds to help predict the quality of the links being degraded.The signal‐to‐interference and noise ratio (SINR) defines the quality of wireless cells by computing the average received power from a signal reference signal, which can represent noise and interference from the network 49 . Xenakis et al 50 presented a two‐tier LTE network handover decision to reduce the transmission energy of mobile terminals.…”
Section: Mobility Management In Heterogeneous Vehicular Networkmentioning
confidence: 99%
“…They identified two thresholds to help predict the quality of the links being degraded.The signal-to-interference and noise ratio (SINR) defines the quality of wireless cells by computing the average received power from a signal reference signal, which can represent noise and interference from the network. 49 Xenakis et al 50 presented a two-tier LTE network handover decision to reduce the transmission energy of mobile terminals. The proposed scheme is dependent on adjusting the handover Hysteresis Margin to a defined signal-to-interference and noise ratio threshold and using the quality measurements of the target cell.…”
Section: Quality-based Ho Solutionsmentioning
confidence: 99%